2020
DOI: 10.1186/s40623-020-01229-8
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the emission altitude of pulsating aurora using the five-wavelength photometer

Abstract: Using a ground-based five-wavelength photometer, which has been operative in Tromsø, Norway since February 2017, we have statistically analyzed the lifetime of O(1 S) to reveal the emission altitude of pulsating aurora (PsA). For the statistics, we have extracted intervals of PsA using an EMCCD all-sky imager on 37 nights during 3 months from January to March, 2018. By performing a cross-correlation analysis between the time-series of 427.8 nm (N 2 + first negative band) and 557.7 nm oxygen emissions, we deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Kawamura et al. (2020) measured a lifetime of oxygen atoms that produce the 557.7‐nm emission by a photometer at Tromsø, Norway. They calculated an altitude of PsAs by using the measured lifetime.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kawamura et al. (2020) measured a lifetime of oxygen atoms that produce the 557.7‐nm emission by a photometer at Tromsø, Norway. They calculated an altitude of PsAs by using the measured lifetime.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible cause is the difference in latitude. Hosokawa and Ogawa (2015) and Kawamura et al (2020), who suggested the increase in the energy of PsA electrons, performed their observations in Tromsø, Norway (MLAT: 66.  7 E…”
Section: Spatial Distribution Of B/g Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2011, Nikon digital cameras (D5000, D5100 and D7200) have been capturing all-sky images almost every night from September to March with a temporal resolution of less than one minute at Ramfjordmoen Research Station in Tromsø, Norway (69.6 • N, 19.2 • E); the station is operated by the UiT -the Arctic University of Norway. These images were not originally planned to be used for a statistical analysis of the auroras, as they were obtained to evaluate weather conditions during the acquisition of atmospheric temperature/wind observations using a sodium LIDAR [37][38][39][40] and multi-wavelength observations of auroras using a photometer [41][42][43] . The digital cameras used were D5000 during 2010-2014, D5100 during 2015, and D7200 during 2016-2021.…”
Section: Optical Observations In Tromsø Norwaymentioning
confidence: 99%
“…There might be the quenching effect on OI 557.7 nm, which could make its emission lifetime shorter (cf. Brekke & Henriksen, 1972; Kawamura et al, 2020; Scourfield et al, 1971). However, their results indicate that the time delay can survive in the case of 557.7 nm.…”
Section: Introductionmentioning
confidence: 99%